Alleviating effects of exogenous melatonin on salt stress in cucumber - Zhang, Tengguo; Shi, Zhongfei; Zhang, Xiaohua; Zheng, Sheng; Wang, Juan; Mo, Jiangnan (Scientia horticulturae, 2020)
•Melatonin effectively alleviate the damage of salt stress on cucumber seedlings.•The alleviation of melatonin to salt stress in cucumber seedlings is related to the production of hydrogen peroxide.•MAP kinase pathway may be involved in melatonin-mediated salt tolerance. Melatonin (N-acetyl-5-methoxytryptamine) is an important molecule in plants that regulates growth and development and responds to abiotic stresses. In this study, we studied the role of exogenous melatonin in alleviating salt stress in cucumber. The results showed that exogenous melatonin pretreatment could improve cell viability, protect photosynthesis, increase antioxidant enzyme activity, inhibit active oxygen explosion, reduce malondialdehyde (MDA) content and relative conductivity in cucumber Seedlings under salt stress compared with salt stress alone. Gene expression analysis showed that melatonin significantly increased the expression of antioxidant enzyme gene, nicotinamide adenine dinucleotide phosphate (NADPH) oxidase genes, mitogen-activated protein kinase (MAPK) genes (MAPK3, MAPK4, MAPK6) and salt overly sensitive (SOS) genes (SOS1, SOS2, SOS3) under salt stress. diphenyleneiodonium (DPI) or dimethylthiourea (DMTU) significantly reduced melatonin-induced defense responses, including decreased antioxidant enzyme activity and photosynthesis protection, as well as the expression of stress-related genes. Similar to DPI and DMTU, U0126 (MEK inhibitor) also reduces melatonin-induced defense responses. In conclusion, our study shows that exogenous melatonin treatment can effectively alleviate the damage of salt stress on cucumber seedlings, and the alleviation effect is related to hydrogen peroxide (H2O2). And there may be interactions between melatonin-mediated salt tolerance and the MAP kinase signaling pathway.